Study on optimization and mechanism of CO2 injection to enhance oil recovery in mid-deep heavy oil reservoirs - Zhang, Xiaokun; Qi, Zongyao; Wang, Bojun; Zhou, You; Wang, Chao; Xi, Changfeng; Liu, Pengcheng (Frontiers in Energy Research, 2024)
In order to improve the oil recovery of mid-deep heavy oil reservoirs, this study investigates the efficiency of enhanced oil recovery and the mechanisms of oil displacement in mid-deep heavy oil reservoirs using different injected gases (N2, CH4, CO2) and development approaches (gas flooding and gas huff-n-puff) through a series of experiments. These experiments include high-pressure physical properties tests of crude oil after gas injection, displacement efficiency tests of gas injection, and displacement efficiency tests of gas huff-n-puff. The results indicate that for mid-deep heavy oil reservoirs, the preferred optimal injection gas is CO2, with gas huff-n-puff being the most effective development method. Furthermore, a numerical simulation study was conducted to explore the adaptability parameters of CO2 huff-n-puff development in different well patterns, encompassing variables such as the amount of gas injected per cycle, crude oil viscosity, reservoir permeability, and oil layer thickness.